Black butler. 16 - Toboso, Yana, 1984- (Yen Press, 2014)
"Earl Ciel Phantomhive and his invincible butler Sebastian may have succeeded in sneaking their way into the elite Weston College, but their investigation quickly hits a wall. To earn an audience with the headmaster, Ciel's only option is to attend the "Midnight Tea Party," an exclusive gathering hosted by the elusive head of the school. And the only way a lowly first-former like Ciel, earl or no, can land a seat at that table is by being elected the Most Valuable Player in the College's annual storied cricket tournament. Selected from each house, students in the springtime of youth battle it out among the wickets on the spring-green lawn. Will the usually unperturbed young earl be bowled over by this unexpected turn of events?"